DESIGN OF FOLDABLE SNACK PACKAGING FOR CHILDREN AS AN EDUCATIONAL MEDIUM FOR WASTE RECYCLING CULTURE - Muhammad Hajid An Nur; Putri Kholida; Hikmal Darma Taruna; Salma Aulia Zahra; Sherina Shifa Maharani; Anita Dora Aurelia (Telkom University, 2026)
This paper presents the design process of foldable snack packaging for children as an educational medium to promote waste recycling culture. The focus lies on the development stages, from conceptual exploration to prototype creation, without extending to testing or validation. The design innovation emphasizes foldability as a strategy to minimize waste volume and incorporates interactive and educational elements to encourage early environmental awareness. Twelve design prototypes were developed based on literature review, patent analysis, and iterative visual experimentation. The study highlights how visual communication design can contribute to sustainability education through packaging innovation. Future studies are encouraged to conduct usability testing and impact evaluation with children as users.